2022
DOI: 10.1080/19490976.2022.2125747
|View full text |Cite
|
Sign up to set email alerts
|

Gut metagenomic characteristics of ADHD reveal low Bacteroides ovatus -associated host cognitive impairment

Abstract: Attention-deficit/hyperactivity disorder (ADHD) is a highly heterogeneous psychiatric disorder that can have three phenotypical presentations: inattentive (I-ADHD), hyperactive-impulsive (HI-ADHD), and combined (C-ADHD). Environmental factors correlated with the gut microbiota community have been implicated in the development of ADHD. However, whether different ADHD symptomatic presentations are associated with distinct microbiota compositions and whether patients could benefit from the correction of aberrant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 71 publications
0
12
0
Order By: Relevance
“…This technology not only allows for more precise identification of the species composition in a sample, but also provides insights into functional composition and metabolic pathways ( Gu et al, 2019 ). Li et al (2022) utilized this approach to sequence 207 human fecal samples and analyzed the gut microbial profiles of ADHD patients with different phenotypes. All the approaches exemplified above will help us to have a deeper understanding of the role of gut microbiota in ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…This technology not only allows for more precise identification of the species composition in a sample, but also provides insights into functional composition and metabolic pathways ( Gu et al, 2019 ). Li et al (2022) utilized this approach to sequence 207 human fecal samples and analyzed the gut microbial profiles of ADHD patients with different phenotypes. All the approaches exemplified above will help us to have a deeper understanding of the role of gut microbiota in ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…Alistipes, primarily isolated from medical clinical samples, is a relatively new genus that is highly relevant in dysbiosis and disease, including mental signs of depression ( Parker et al., 2020 ). A recent study revealed gut microbiota characteristics of ADHD and found that low levels of Bacteroides ovatus were associated with host cognitive impairment ( Li et al., 2022 ). Bacteroides ovatus colonization has also been reported to influence the abundance of intestinal short-chain fatty acids and neurotransmitters ( Horvath et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Only two studies used shotgun metagenomics sequencing which could provide additional information of gut microbiota species to better understand its role in ADHD (Y. Li et al, 2022;Wang et al, 2022). We performed meta-analyses for these results, and found outcomes varied greatly between studies (Wang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The latest 10 researches investigated the possible correlation between the gut microbiota and ADHD, but researchers still have not reached consistent conclusions (Aarts et al, 2017; Jiang et al, 2018; Y. Li et al, 2022; Prehn-Kristensen et al, 2018; Richarte et al, 2021; Szopinska-Tokov et al, 2020; Wan et al, 2020; Wang et al, 2020, 2022; Zhou et al, 2021).…”
Section: Introductionmentioning
confidence: 99%